Exploring the Argumentation Level in Inquiry Learning of Force and Motion - Dyah Permata Sari; Madlazim Madlazim (Jurnal Inovasi Pendidikan Sains (JIPS), 2022)
One of the learning methods that is proven to be able to develop and improve students' critical thinking skills is to apply an argumentation strategy with ADI (Argumentation-Driven-Inquiry). This study aims to investigate the level of student argumentation on the subject of motion and force. This study focused on identifying the level of student argumentation after the ADI model was applied. The research population was students of Physics Education, Surabaya State University, whose year class is 2020. The sample selection used a random sampling cluster technique. The used instrument consisted of a multiple-choice test with 10 questions and 2 essays to determine the level of student argumentation. The results showed that the students' arguments were at level 3, namely the ability to analyse problems related to motion and force. Based on the results of the study, it can be concluded that the argumentation abilities of students who do not contribute to give argumentation or who are at level 1, are not able to answer analytical questions about motion and force phenomena properly. Meanwhile, students who are at level 2 are still fixated on one concept or method, and still have difficulty when trying to apply other methods to solve problems. Students whose argumentation are at level 3, 4, and 5 have been able to fulfil all the characteristics of critical thinking, but some still have weaknesses, namely the ability to analyse motion and force problems.